Gorillas in the midst of man (Kuala Lumpur : Vision Four Home Video, 1993)
A documentary film on gorilla showing their progress, charting the feeding, resting, breeding and socializing habits.
Photography, Neil Rettig.
Narrated by Brian Blessed.
Keywords: Gorillas